RELATIONSHIP ANALYSIS BETWEEN KNOWLEDGE, FACILITIES AND BEHAVIOR OF HOUSEHOLD WASTE MANAGEMENT AND INCIDENCE OF TODDLERS’ DIARRHEA IN SEDAH KIDUL VILLAGE - Wardatul Raihan; Trias Mahmudiono (Universitas Airlangga, 2022)
Introduction: Determinants of health consist of social and physical determinants; one the factors included in physical determinants is environment. Environmental conditions that aren’t healthy can attract flies to land. Diarrhea is caused by vectors (flies) that contaminate food and drink consumed by humans. This research aimed to analyze the strength of the relationship between knowledge, facilities, and behavior of household waste management with the incidence of diarrhea in toddlers in Sedah Kidul Village. Methods: This research was a descriptive study with a quantitative approach and a cross-sectional study design. Respondents were selected using simple random sampling from families with toddlers in Sedah Kidul Village as many as 40 respondents. The questionnaire was distributed to respondents to obtain research data. The statistical test used was the contingency coefficient to analyze the strength of the relationship between the variables tested. Result: The results showed the strength of the relationship for level of knowledge (p-value = 0.373 and C = 0.269) including the weak category, availability of facilities (p-value = 0.380 and C = 0.267) including the weak category, and household waste management behavior (p-value = 0.763 and C = 0.168) including the very weak category with the incidence of toddler diarrhea. Conclusion: The conclusion based on the results of statistical tests is there was no significant relationship between knowledge, facilities, and behavior of household waste management with the incidence of toddler diarrhea, supported by the strength category of the relationship on the three variables.